(untitled) (Abhat Journal, 2023)
The analogy is a depiction that reveals the reality of the aesthetic situation that the poet suffered during the process of creativity, and draws the dimensions of that situation through the approach between the two sides of the analogy and the decorative analogy, which is the finest type of analogy. , so that there is a difference between the naive and the rare private, and the artistic taste is what determines the angle from which the poet looks at the external scene that he wants to draw and identifies the tools that play a special role in this depiction, as it suggests the distribution of lines, shadows and colors that he uses, And the decorative analogy gains its importance from its scarcity and strangeness, in order to be able to arouse surprise and admiration in the hearts of the recipients, and its scarcity and strangeness are at the heart of the aesthetic truth of the text.